DAMAGE TO THE SPINE AND SPINAL CORD AND THEIR TREATMENT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Relevance of the study. Injuries to the spine and spinal cord are due to the high frequency of damage, the severity of the clinical course and the difficulty of treating this category of patients. In addition, the presence of a higher percentage of disabilities affects the labor force and causes great economic damage to the national economy. (T.E. Ungbaev 1986, A.B. Bolgaev 2000,2010,2023). Relevance of the study. Injuries to the spine and spinal cord are due to the high frequency of damage, the severity of the clinical course and the difficulty of treating this category of patients. In addition, the presence of a higher percentage of disabilities affects the labor force and causes great economic damage to the national economy. (T.E. Ungbaev 1986, A.B. Bolgaev 2000,2010,2023).